PENGARUH STATUS PENGUASAAN LAHAN TERHADAP PRODUKSI PADI SAWAH TADAH HUJAN DI KABUPATEN BANYUMAS - Rifki Andi Novia; Ratna Satriani (Universitas Medan Area, 2020)
This study aimed to determine the effect of agricultural land tenure status on rainfed lowland rice production in Banyumas Regency. One of the most important factors of production affecting the production of rainfed lowland rice is the land used. This study used survey method by taking primary data and secondary data. Primary data obtained through a list of questions that have been prepared, while secondary data obtained from the relevant agencies. The sampling method is carried out by stratified random sampling. Each stratum of the sample is drawn with a total sample of 50 farmer respondents. Data were analyzed used one-way analysis of variance (One-way ANOVA). The results of this study indicated that the amount of rainfed lowland rice production in Banyumas District showed significant difference between farmers who were not owners and farmers who own land. Non-owner farmers get an average production yield greater than those of farmers who own rainfed lowland rice in Banyumas Regency.